Ischemia of the Penis and Fingertips Secondary to Calcifying Uremic Arteriolopathy - Jroundi, Hatim (Cureus, 2020)
Calcifying uremic arteriolopathy (CUA), also called calciphylaxis, refers to the calcification of the walls of the arteries of medium and small caliber, causing ischemic skin lesions. Diagnosis should be made if ischemic lesion develops in a patient with chronic renal failure (CRF), and it is confirmed based on clinical, radiological, and histological criteria. Generalized CUA characterized by ischemia of the penis (IP) along with other localizations of cutaneous ischemia is exceptional, and the morbidity and high mortality rate associated with this entity most often warrant multidisciplinary and conservative management.